How to achieve the long-term goals of EUS training——survey on the performance of diagnostic EUS by newly trained endosonographers and analysis of the influencing factors - Song Zhang; Congqiang Shen; Shanshan Shen; Yonghua Shen; Lei Wang; Ying Lv (BMC Medical Education)
Abstract Objectives This study endeavors to evaluate the integration of endoscopic ultrasonography (EUS) by trainees upon their return to the hospital and discern the influencing factors. Methods A questionnaire survey was administered to trainees who completed EUS training at the Department of Gastroenterology, Nanjing Drum Tower Hospital from October 2016 to April 2022. The impact of various factors, including trainees’ characteristics, working conditions, and EUS procedure numbers during training was analyzed. Results 65 valid questionnaires were categorized into two groups based on the median number of EUS procedures performed by trainees within one year post-training: a group with fewer EUS cases (< 30 cases) and a group with more EUS cases (≥ 30 cases). Significant differences were found in annual EUS procedures (P < 0.001), endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) cases (P < 0.001), and complete scan rates (P = 0.007). Favorable conditions for trainees in performing EUS included higher-level hospitals (P = 0.001), more hospital beds (P = 0.015) and department beds (P = 0.033), greater annual endoscopy volume (P < 0.001), a longer prior duration of the use of EUS on the hospital (P = 0.003), higher departmental EUS volume (P < 0.001) and presence of established staff endosonographers (P < 0.001). Additionally, trainees in the group with more EUS cases had more guidance from experienced colleagues (P = 0.009). Multivariate logistic regression analysis highlighted annual endoscopy volume and EUS volume as independent influencing factors. Conclusion Tertiary hospitals with larger bed capacities and high endoscopy volumes foster optimal EUS skill development among trainees. Moreover, factors such as longer duration of EUS implementation, increased caseload and guidance from experienced colleagues all contribute to the professional growth of trainees. Clinical trial number Not applicable.